Orientasi Komitmen Ditinjau dari Kepemimpinan Transformasional & Kepercayaan Terhadap Manajemen - Sumaryono Sumaryono; Djamaludin Ancok (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2005)
This research aimed at finding Human Resources Management pattern in Indonesian business organization, like BUMN. Focus of the research were finding correlation pattern between commitment orientation with trust for management and transformational leadership. This research also assesed about carrier-oriented commitment, team-oriented commitment, and organizational-oriented commitment.  Data were collected from 208 employees at BUMN in East Java.  One of the reasons, organization climate was conducive for change. Furthermore, three scales used in this research: Orientation Commitment Scale, Trust for Management Scale, Transformational Leadership Scale. Data analysis is regression analysis.    The results of the research are: a) Transformational Leadership and trust for management correlate with Commitment Orientation, b) Carrier-Oriented Commitment was influenced by trust for management, c) Transformational Leadership and trust for management correlate with Team-Oriented Commitment, when, d) Organizational-Oriented Commitment was influenced by Transformational Leadership.Key Words: Commitment Orientation, Transformational Leadership.